MAKTABGACHA YOSHDAGI BOLALARGA INNOVATSION YONDOSHUV ASOSIDA GEOMETRIK SHAKLLARNI O’RGATISH USULLARI - Vaxabova Gulshan Vafoqul qizi (Journal Park Publishing, 2023)
This article is dedicated to "Methods of improving preschool children's learning of geometric shapes based on innovative approach". It covers issues such as the differentiation and perception of geometric shapes by preschool children, the formation of ideas about geometric shapes, the shapes of objects, their properties, size, height, width, and height. It is aimed at developing innovative approaches to the formation of mathematical images by improving the methods of learning geometric shapes in preschool children.
Keywords: Geometric shapes, triangle, rectangle, square, sensory education, oval, cube, spatial figures.